THE SIGNIFICANCE AND POTENTIAL OF AUTOMATION IN MODERN MANUFACTURING (Eureka Journal of Artificial Intelligence and Data Innovation, 2025)
This article examines the role of automation in enhancing production efficiency, reducing errors, improving product quality, and optimizing resource utilization, based on an analysis of the historical development of manufacturing automation, key methodologies, and contemporary technologies. The study explores the opportunities and limitations of implementing modern technologies in production, such as computer control, robotics, numerical control systems (CNC), programmable logic controllers (PLC), artificial intelligence (AI), and the Internet of Things (IoT). Special attention is given to social changes in the labor market. The research also comprehensively considers the economic and social challenges associated with automation, as well as its potential for creating new employment opportunities.
Keywords: Manufacturing process automation, robotics, CNC, PLC, artificial intelligence, IoT, production efficiency, resource optimization, labor market changes, emerging technologies, economic and social impacts.